2014
DOI: 10.1590/0004-2730000002853
|View full text |Cite
|
Sign up to set email alerts
|

Uso da FISH em mucosa oral para investigação de mosaicismo com linhagem 45,X: estudo com homens saudáveis e pacientes com distúrbios da diferenciação do sexo

Abstract: Objetivo: Verificar se a hibridização in situ por fluorescência (FISH) em células de mucosa oral poderia ser empregada para detectar criptomosaicismo com linhagem 45,X em pacientes 46,XY. Sujeitos e métodos: Amostra de 19 jovens saudáveis 46,XY e cinco pacientes com distúrbios da diferenciação do sexo (DDS), quatro 45,X/46,XY e um 46,XY. FISH com sondas específicas para X e Y em núcleos interfásicos de linfócitos e mucosa oral para investigar a proporção de núcleos contendo apenas o sinal do cromossomo X. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…This study also showed that using mouth epithelial cells may be efficient for this kind of analysis and advantageously evaluates a tissue with the same embryo origin as fibroblasts without the need for biopsy or culturing. Yet, it requires same-day processing to avoid bacterial contamination (16).…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that using mouth epithelial cells may be efficient for this kind of analysis and advantageously evaluates a tissue with the same embryo origin as fibroblasts without the need for biopsy or culturing. Yet, it requires same-day processing to avoid bacterial contamination (16).…”
Section: Discussionmentioning
confidence: 99%